2007
DOI: 10.1021/es062155y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response Concentration-Controlled Desorption of Activated Carbon to Dampen Concentration Fluctuations

Abstract: Fluctuations in concentration of organic vapors in gas streams that are treated by devices such as biofilters or oxidizers make it challenging to remove the vapors from the gas streams in an efficient and economic manner. Combining adsorption with concentration-controlled desorption provides an active buffer between the source of vapors and the control device for better control of concentration and flow rate of the gas stream that is treated by the secondary control device, hence further enhancing the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Resistance heating has been shown to be a more rapid and energy-efficient method of regenerating activated carbon than desorbing with steam or inert gas (Petkovska and Mitrovic 1994). Because of this, ACFCs have been studied recently in an effort to develop next-generation energy-efficient cyclic adsorption systems (Subrenat and Le Cloirec 2006;Vidal et al 2006;Hashisho et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance heating has been shown to be a more rapid and energy-efficient method of regenerating activated carbon than desorbing with steam or inert gas (Petkovska and Mitrovic 1994). Because of this, ACFCs have been studied recently in an effort to develop next-generation energy-efficient cyclic adsorption systems (Subrenat and Le Cloirec 2006;Vidal et al 2006;Hashisho et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of separation methods such as condensation, adsorption, catalytic oxidation, and biofiltration have been employed to remove a number of pollutants from the air stream . Adsorption processes constitute an important class of separation processes that are typically low in energy consumption .…”
Section: Introductionmentioning
confidence: 99%
“…Because phenol oligomerization necessitates the use of high regeneration temperatures, the authors consistently experienced pore blockage and corresponding decreases in adsorption capacity during subsequent use, attributed to phenol decomposition during regeneration. For gas-phase studies, nondestructive regeneration using microwave heating has been shown, but only for low molecular weight, low boiling point adsorbates (e.g., methane, ethane, ethylene, methyl ethyl ketone, water). For many industrial applications, however, heavy compounds (e.g., n -dodecane, ethylbenzene, and 1,2,4-trimethylbenzene) are present in the gaseous VOC mixtures and often have high affinity for the adsorbent, requiring more intense regeneration conditions (i.e., higher temperature, longer times) for complete regeneration . It would be beneficial to evaluate whether microwave regeneration can be similarly efficient and nondestructive when desorbing high molecular weight, high boiling point contaminants.…”
Section: Introductionmentioning
confidence: 99%